POETICS OF CONTRADICTORY MEANS IN THE UZBEK LANGUAGE (Scientific journal of the Fergana State University, 2023)
Today, lexopoetics is one of the areas that require special research in the framework of linguistic and poetic research. In recent years, in the field of linguopoetics, the artistic and aesthetic functions of lexical units used in works of art have been comprehensively analyzed. This article is devoted to the poetics of conflict means in a literary text. In linguo-poetic research, in relation to the form and meaning of word types, one can analyze the performance of poetic tasks, such as artistry, imagery and melodiousness of words and phrases that are opposite in meaning, synonyms and similar forms in a poetic text. Words with the opposite meaning are one of the means that provide expressiveness and effectiveness of artistic speech. Object of study: the text of poetic works by A. Abidjan. Subject of study: linguistic and poetic features of lexical units in the text of a work of art. Research method: system-structural analysis of language level units. On the example of the poetry of A. Abidjon, which is the object of this study, the author's ability to use conflict means is studied.